The sinful side of taxation : is it possible to satisfy the government hunger for revenues while promoting economic growth? - Alves, José (2018)
In this study we try to evaluate both linear and non-linear relationships between each tax item and real per capita growth. Our analysis, conducted for all the OECD countries between 1980 and 2015 and by resorting to panel data techniques in a short and long-term basis, evidences tax items threshold values for all tax components (except for taxes on individual income). In particular, for long-run economic performance, we obtain optimal threshold values for social security contributions between 7.0% and 12.43%. Lastly, our results provide some conclusions, highlighting the raise of some taxes, in GDP terms, without harming economic growth evolution.